O processo coletivo e o desafio da litigância massificada - VALENTE, Bruno Araújo Soares (Universidade Federal do Pará, 2018)
The paper, starting from an overview of the impact that the intense social changes in recent decades (which led significant current sociologists and philosophers to identify the emergence of a new paradigm, named of postmodernity) resulted on the legal reality, focuses its analysis on one of them, namely, the repetitive or mass litigation, defending the use of so-called collective process as the most appropriate instrument to face the challenges that arise. To this end, it seeks to demonstrate, as theoretical premises, which are the system and principle concepts more consistent with the current stage of development of the science of law. Then, after setting the basic contours of the notion of collective process with which to work, going to study the theoretical and practical aspects of mass litigation phenomenon and, finally, demonstrate the reasons why the collective process is the best way to processing, even not being the path taken by national legislation and jurisprudence.